Wild places : the life of naturalist David Attenborough - Rocco, Hayley (G.P. Putnam's Sons, an imprint of Penguin Random House LLC, 2023)
"A nonfiction account of the life of British naturalist David Attenborough and his advocacy for the protection of wild places on Earth"--